Performance evaluation of Human Immunodeficiency Virus Type 1 RNA Quantitative Diagnostic Kit assay: Performance evaluation of HIV-1 real-time PCR commercial kit - Vázquez, Alicia Fleites; Guevara, María Teresa Pérez (Brazilian Journal of Sexually Transmitted Diseases, 2025)
Introduction: Quantitative determination of human immunodeficiency virus (HIV) concentration is an important parameter for the prognosis and treatment of infected people, contributing to understanding the infection’s pathogenesis. The quantitative real-time polymerase chain reaction (qPCR) methodology offers numerous advantages over traditional molecular methods for measuring HIV viral load. In Cuba, the HIV Type 1 RNA Quantitative Diagnostic Kit was developed as an additional option to the existing technology for HIV-1 RNA determination. Objective: This work aimed to evaluate the performance of the HIV Type 1 RNA Quantitative Diagnostic Kit (PCR - Fluorescence Probing) for quantitative detection of HIV-1 RNA in human samples. Methods: We evaluated human serum and plasma samples previously characterized by molecular techniques. Five panels of HIV positive and negative samples were used for studies of concordance, diagnostic sensitivity, clinical and analytical specificity, intra- and inter-assay precision, and linearity and robustness. We also evaluated an international standard for testing analytical sensitivity. Results: Concordance, diagnostic sensitivity, and specificities resulted in 100% reliability. Coefficients of variation of less than 20% and 17% were obtained in intra- and inter-assay precision, respectively. The analytical sensitivity was 32.4 IU/mL, inferior to that established by the producer (50 IU/mL). The assay showed linear behavior, and the robustness was confirmed by performing the technique by different operators in different equipment and laboratories. Conclusion: The results demonstrate the feasibility of using the HIV Type 1 RNA Quantitative Diagnostic Kit for the quantitative detection of HIV-1 RNA in human serum or plasma samples.